2009
DOI: 10.1111/j.1744-9987.2009.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of High‐Throughput Leukocytapheresis for Rheumatoid Arthritis With a Reduced Response to Infliximab

Abstract: Infliximab (INF), a tumor necrosis factor-alpha (TNF-alpha) inhibitor, is an effective drug for patients with rheumatoid arthritis (RA). However, some patients receive no clinical benefit, or the agents gradually lose their effect. Five sessions of high-throughput leukocytapheresis (LCAP) were given at a frequency of once a week using a Cellsorba CS-180S to four patients with a reduced response to INF. The clinical response to LCAP was evaluated using the 28-joint disease activity score with C-reactive protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…In the present study, changes in PD findings by LCAP correlated with changes in evaluator's global assessment and swollen joint count but not with those in CRP or ESR. The results of the present study are similar to those of previous findings (11,23,24) and showed that LCAP inhibits synovitis even in RA patients without decreases in CRP systemic inflammatory reaction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, changes in PD findings by LCAP correlated with changes in evaluator's global assessment and swollen joint count but not with those in CRP or ESR. The results of the present study are similar to those of previous findings (11,23,24) and showed that LCAP inhibits synovitis even in RA patients without decreases in CRP systemic inflammatory reaction.…”
Section: Discussionsupporting
confidence: 93%
“…Correlations between changes of PDUS findings and those of DAS28, CRP, and ESR by anti-TNF-α therapy have been reported (9,21). Among the components of the DAS or Simplified Disease Activity Index, LCAP is marked by decreases in tender joint count, swollen joint count, patient's global assessment, and evaluator's global assessment but by slight decreases in CRP and ESR (11,23,24). In the present study, changes in PD findings by LCAP correlated with changes in evaluator's global assessment and swollen joint count but not with those in CRP or ESR.…”
Section: Discussionmentioning
confidence: 99%
“…By cytapheresis, inflammatory cells (granulocytes, monocytes, or lymphocytes) or platelets are depleted from the peripheral blood. Cytapheresis has been successfully applied in rheumatoid arthritis, systemic lupus erythematosus, and inflammatory bowel disease (7–9). In dermatology, patients with psoriasis and pyoderma gangrenosum have been successfully subjected to leukocytpheresis (10,11).…”
mentioning
confidence: 99%
“…Leukapheresis has also been proposed as a therapy for some autoimmune diseases such as rheumatoid arthritis (Sakai et al, 2009). However, the long-term effect of such therapy is unknown.…”
Section: Discussionmentioning
confidence: 99%